Nursing education in the Czech Republic - Tóthová, Valérie; Sedláková, Gabriela (Nurse education today, 2008)
The report is focused on the transformation process in pregraduate education of nurses in the Czech Republic. The all-society changes taking place in the last decades of the 20th century have opened the way for implementation of changes in the Czech nursing as well. Nursing is becoming an independent scientific discipline, the role of the nurses and their position in the society are changing and the professional preparation is gradually shifting to colleges and universities. After 15 years of effort to implement the planned transformation changes in nursing education, the Czech Republic's joining of the European Union has helped us. In connection with fulfillment of Bologna declaration, Master study in nursing has been gradually developing in education of nurses in the Czech Republic as well. In order to create a structured study in nursing according to the above mentioned declaration, a postgraduate doctor program must be implemented too. The implementation of all types of university education of nurses is very important and it will positively contribute to the development of nursing in our republic as a full-bodied scientific discipline and to the creation of its high-quality scientific-research base.
Keywords: studium ošetřovatelství bakalářské; Curriculum; kurikulum; Education, Nursing; studium ošetřovatelství; lidé; Education, Nursing, Baccalaureate; studium ošetřovatelství vysokoškolské; Education, Nursing, Graduate; Humans